Concomitant dengue fever in varicella zoster infection - a rare presentation - Shalihin, Mohd Shaiful Ehsan; Ahmad Radzi, Mohd. Ashrafuddin; Osman, Iskandar Firzada (2018)
Fever and rashes are among the common symptoms in primary care. The characters of the fever and onset of rashes would be the important clues in making a diagnosis [1].  Varicella Zoster virus infection in children is generally a mild disease in which they tend to be afebrile within few days of illness. Therefore, other concomitant illness need to be rule out if the fever is persistent [1].  Dengue Fever (DF) can be asymptomatic but typically presented with mild febrile illness and other broad range of manifestations. Without proper monitoring and adequate hydration, patient may end up in life threatening shock.  DF is a public concern and the responsibility of early detection falls on Primary Care Providers (PCP). A high index of suspicion is really needed even in a patient who had been diagnosed with other type of infectious disease earlier as in our case.  We would like to report a case of a rare presentation of concomitant Dengue Fever without warning sign of a pre-school children with a background of Varicella Zoster infection who initially presented to us with fever and vesicular rashes.